2019
DOI: 10.1177/0269881119860666
|View full text |Cite
|
Sign up to set email alerts
|

Cortical 5-hydroxytryptamine 1A receptor biased agonist, NLX-101, displays rapid-acting antidepressant-like properties in the rat chronic mild stress model

Abstract: Background: NLX-101 (also known as F15599) is a highly selective and efficacious ‘biased’ agonist at cortical 5-hydroxytryptamine 1A (5-HT1A) heteroreceptors. In rodents, it possesses marked antidepressant-like activity, potently and completely abolishing immobility in the forced swim test (FST) with extended duration of action. Methods: We investigated the antidepressant-like activity of NLX-101 using the rat chronic mild stress (CMS) model of depression, considered to have a higher translational potential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 72 publications
6
18
0
Order By: Relevance
“…Moreover, we administered the compounds acutely as we intended to show similarities between the studied biased 5-HT 1A agonists and rapid-acting ketamine. However, considering that neither F15599 nor F13714 reversed the stressed mice's anhedoniclike behavior in the SPT and based on studies in rats (Depoortère et al 2019), we may speculate that the compounds need to be administered at least twice or chronically. This issue will require future studies.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, we administered the compounds acutely as we intended to show similarities between the studied biased 5-HT 1A agonists and rapid-acting ketamine. However, considering that neither F15599 nor F13714 reversed the stressed mice's anhedoniclike behavior in the SPT and based on studies in rats (Depoortère et al 2019), we may speculate that the compounds need to be administered at least twice or chronically. This issue will require future studies.…”
Section: Discussionmentioning
confidence: 97%
“…The agonists did not, however, reverse the anhedonic-like deficit in the sucrose preference test in the stressed mice, unlike ketamine. As a comparison, a recent study in rats by Depoortère et al (2019) showed that F15599, administered ip twice daily, reversed the chronic mild stress-induced decrease in sucrose intake. This was observed from day 1 of testing and was maintained throughout the 2 weeks of treatment and up to 4 weeks after cessation of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent preclinical studies have demonstrated that the administration of the highly selective 5-HT 1A receptor biased agonist, NLX-101 (also known as F15599), results in a rapid antidepressant-like response, both in naïve animals [ 12 , 13 ] and rodent models of depression [ 14 , 15 ], presumably through the activation of cortical 5-HT 1A receptors. Indeed, direct cortical microinjection of NLX-101 reduced immobility in the forced swim test, an effect that was blocked by the selective 5-HT 1A receptor antagonist, WAY-100635 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%